Education and Human Resource Development for Improving the Reputation of Higher Education Institutions - Salamun, Salamun; Masrur, Moh; Muhtarom, Muhtarom (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
This study explores the importance of Human Resource (HR) development in contributing to a university's reputation. This research is qualitative in the form of library research. From the study, it was concluded that improving a university's reputation is highly prioritized through the development of human resources carried out informally and formally. Informally, this effort can be done through self-development programs like training. It can be done by increasing education by continuing studies in the doctoral program (S3). Improving and developing academic qualifications is essentially a personal obligation for each lecturer, so each lecturer is highly recommended to develop a self-development curriculum (KPD) mainly related to developing and implementing the Tri Dharma of Higher Education.